That is my dream! : a picture book of Langston Hughes's "Dream variation" - Hughes, Langston, 1902-1967 (Schwartz & Wade Books, 2017)
"Dream Variation," one of Langston Hughes's most celebrated poems, about the dream of a world free of discrimination and racial prejudice, is now a picture book stunningly illustrated by Daniel Miyares ... An African-American boy faces the harsh reality of segregation and racial prejudice, but he dreams of a different life--one full of freedom, hope, and wild possibility, where he can fling his arms wide in the face of the sun"--